2000
DOI: 10.1126/science.289.5477.270
|View full text |Cite
|
Sign up to set email alerts
|

Causes of Climate Change Over the Past 1000 Years

Abstract: Recent reconstructions of Northern Hemisphere temperatures and climate forcing over the past 1000 years allow the warming of the 20th century to be placed within a historical context and various mechanisms of climate change to be tested. Comparisons of observations with simulations from an energy balance climate model indicate that as much as 41 to 64% of preanthropogenic (pre-1850) decadal-scale temperature variations was due to changes in solar irradiance and volcanism. Removal of the forced response from re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

58
1,395
2
44

Year Published

2003
2003
2015
2015

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 1,841 publications
(1,533 citation statements)
references
References 80 publications
58
1,395
2
44
Order By: Relevance
“…This effect is most prominent on the longer (centennial) time scales in the model of Zorita and González-Rouco (2002). But even on decadal scales this effect should be present, because volcanic eruptions caused decadal temperature variations during that period (Crowley 2000). The years around 1715 mark the end of the Late Maunder Minimum, where major changes in the solar and volcanic forcing occurred and Northern Hemisphere temperatures showed large variations (Lean et al 1995;Mann et al 1998;Crowley 2000;Luterbacher et al 2001;Shindell et al 2001).…”
Section: Discussionmentioning
confidence: 99%
“…This effect is most prominent on the longer (centennial) time scales in the model of Zorita and González-Rouco (2002). But even on decadal scales this effect should be present, because volcanic eruptions caused decadal temperature variations during that period (Crowley 2000). The years around 1715 mark the end of the Late Maunder Minimum, where major changes in the solar and volcanic forcing occurred and Northern Hemisphere temperatures showed large variations (Lean et al 1995;Mann et al 1998;Crowley 2000;Luterbacher et al 2001;Shindell et al 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Based on comparisons between simple climate model simulations and reconstructions of Northern Hemisphere temperature changes since 1000, Crowley (2000) showed that a large part of the decadal-scale temperature VOLUME 16 J O U R N A L O F C L I M A T E variability in preindustrial climate could be explained by changes in solar irradiance and volcanism. A simulation including just solar irradiance changes alone (Rind 2002) indicates that in some periods (such as the eighteenth century) solar forcing was more likely to be important whereas in other periods (such as the nineteenth century) volcanism probably played a greater role, although another study indicates that volcanic forcing was generally dominant (Hegerl et al 2003).…”
Section: Introductionmentioning
confidence: 99%
“…This increase of CO 2 level in the atmosphere exceeds the natural variability of the past 1000 years (Crowley, 2000). The main reason for the observed drastic increase of CO 2 levels is due to the consumption of fossil fuels (Houghton et al, 2001a).…”
Section: Global Carbon Cycle and Climate Changementioning
confidence: 97%